Microwave-assisted hydrothermal synthesis of Bi2S3 nanorods in flower-shaped bundles - Titipun Thongtem (2018)
Bi2S3nanorods in flower-shaped bundles were successfully synthesized from the decomposition of Bithiourea complexes under the microwave-assisted hydrothermal process. X-ray powder diffraction (XRD) patterns and field emission scanning electron microscopy (FE-SEM) show that Bi2S3has the orthorhombic phase and appears as nanorods in flower-shaped bundles. A transmission electron microscopic (TEM) study reveals the independent single Bi2S3nanorods with their growth along the [0 0 1] direction. A possible formation mechanism of Bi2S3nanorods in flower-shaped bundles is also proposed and discussed. Their UVvis spectrum shows the absorbance at 596 nm, with its direct energy band gap of 1.82 eV. © 2009 Elsevier B.V.